2021
DOI: 10.1063/5.0057343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the aspect ratio on the velocity field of a straight open-channel flow

Abstract: This study investigates numerically the effect of the aspect ratio (AR) on the velocity field characteristics of the turbulent flow of a straight open-channel flow. Five aspect ratio cases (AR = channel width/flow depth) are investigated ranging from a narrow case of AR = 1 to a wide case of AR = 9. The transient three-dimensional Navier–Stokes equations were numerically solved using a finite-volume approach with an improved–delayed detached-eddy simulation turbulence model. The objective of this study is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Most of the previous studies focused on the influence of turbulence-driven secondary currents on the narrow channel flow characteristics were under subcritical flow conditions and a r ! 2, except a few experimental studies (Auel et al, 2014;Demiral et al, 2020;Jing et al, 2019;Nezu and Nakagawa, 1986;Nezu and Rodi, 1985;Rajaratnam and Muralidhar, 1969) and numerical studies (Nasif et al, 2020;Shinneeb et al, 2021), which engaged supercritical flows as discussed in Table I. Recently, Demiral et al (2020) reported four well-developed vortices at each half of the channel width under decelerating flow conditions for Fr from 1.84 to 3.33 and a r from 0.89 to 1.91.…”
Section: Studies On the Supercritical Narrow Channel Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies focused on the influence of turbulence-driven secondary currents on the narrow channel flow characteristics were under subcritical flow conditions and a r ! 2, except a few experimental studies (Auel et al, 2014;Demiral et al, 2020;Jing et al, 2019;Nezu and Nakagawa, 1986;Nezu and Rodi, 1985;Rajaratnam and Muralidhar, 1969) and numerical studies (Nasif et al, 2020;Shinneeb et al, 2021), which engaged supercritical flows as discussed in Table I. Recently, Demiral et al (2020) reported four well-developed vortices at each half of the channel width under decelerating flow conditions for Fr from 1.84 to 3.33 and a r from 0.89 to 1.91.…”
Section: Studies On the Supercritical Narrow Channel Flowsmentioning
confidence: 99%
“…developed subcritical flow conditions and relatively low Reynolds number Re [except Nasif et al (2020) and Shinneeb et al (2021)]. Cokljat (1993) used the nonlinear k-e model (where k-turbulent kinetic energy and e-dissipation rate of k) to close the turbulence equations of Reynolds-averaged Navier-Stokes (RANS) simulations, whereas Naot and Rodi (1982) used ASM-RANS; Cokljat and Younis (1995), Cokljat (1993), Kang andChoi (2006), andReece (1977) used RSM-RANS; Nasif et al (2020) and Shinneeb et al (2021) used detached-eddy simulation (DES); Broglia et al (2003) and Shi et al (1999) used LES;and Nikitin (2021) used DNS. Apparently, the free surface effect was underestimated in both DES studies as discussed in Table I.…”
Section: Different Modeling Approachesmentioning
confidence: 99%
“…In the following results, x-, y-, and z-axes represent streamwise, vertical, and horizontal locations respectively; while U, V, and W represent the corresponding mean velocity components. It should be noted that the computational results of the open channel flow presented in sections 5.1-5.3 were already discussed in Shinneeb et al, [5,22], and is presented here for completeness.…”
Section: Resultsmentioning
confidence: 76%
“…Nezu et al, [4] investigated the formation of secondary currents in a smooth rectangular open channel flow by varying the aspect ratio. Shinneeb et al, [5] reported the formation of a pair of counter-rotating recirculation zones near the corners of a flume whose size is a function of the AR. One recirculation zone resides above the corner bisector-line which is called the "side-recirculation zone (SRZ)", and the other one resides under the bisector-line which is called the "bottom-recirculation zone (BRZ)".…”
Section: Introductionmentioning
confidence: 99%
“…Available data from previous experiments are used to validate the numerical results. The width of the channel in this study is broad enough so that the effect of the secondary currents is negligible at the channel central plane [10].…”
Section: Introductionmentioning
confidence: 99%